2020
DOI: 10.1107/s2052520619016287
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular insight into the substitution of sulfur by selenium, based on crystal structures, quantum-chemical calculations and biosystem recognition

Abstract: Statistical analysis of data from crystal structures extracted from the Cambridge Structural Database (CSD) has shown that S and Se atoms display a similar tendency towards specific types of interaction if they are part of a fragment that corresponds to the side chains of cysteine (Cys), methionine (Met) selenocysteine (Sec) and selenomethionine (Mse). The most numerous are structures with C-HÁ Á ÁSe and C-HÁ Á ÁS interactions ($80%), notably less numerous are structures with SeÁ Á ÁSe and SÁ Á ÁS interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…This percentage is an underestimate as in the present survey as crystals where Se … O interactions were acting in concert with other identifiable intermolecular forces, the notable example being hydrogen bonding, were omitted. This percentage compares favourably to the 6% of selenium(lone-pair) … π(arene) interactions in crystals where these interactions can potentially form [248] , [249] . Over and above different chemical composition, as alluded to above, secondary bonding interactions, including chalcogen bonding interactions, are notoriously subject to steric effects in that these interactions are mitigated when bulky metal-bound and/or ligand-bound substituents are present [54] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] .…”
Section: Overviewmentioning
confidence: 80%
“…This percentage is an underestimate as in the present survey as crystals where Se … O interactions were acting in concert with other identifiable intermolecular forces, the notable example being hydrogen bonding, were omitted. This percentage compares favourably to the 6% of selenium(lone-pair) … π(arene) interactions in crystals where these interactions can potentially form [248] , [249] . Over and above different chemical composition, as alluded to above, secondary bonding interactions, including chalcogen bonding interactions, are notoriously subject to steric effects in that these interactions are mitigated when bulky metal-bound and/or ligand-bound substituents are present [54] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] .…”
Section: Overviewmentioning
confidence: 80%
“…Fzf1p is composed of five zinc fingers (ZFs) and plays a positive role in the transcription of ssu1 ( 26 ). Given the tight regulatory relationship between ssu1 and fzf1 and that they were both mutated in most evolved groups within several positions coincidentally, these results suggested that ssu1 and fzf1 are likely to perform homogeneous functions in selenium metabolism combined with the chemical similarity between selenium and sulfur ( 27 29 ). Therefore, we investigated the latent functions of ssu1 and fzf1 in the selenium tolerance of yeasts and then confirmed that both ssu1 and fzf1 indeed play vital roles, while the other four most frequently mutated genes ( fcy21 , cos9 , mnn4 , and bio3 ) screened by sequencing analysis were found to be irrelevant for selenium tolerance (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…for delocalised [97] selenium(lone-pair) … π(arene) interactions [45,198]; both these surveys allowed for the presence of multi-nuclear selenium compounds. As performed for the recent survey of Se … O secondary-bonding interactions [50], specific classes of compounds were evaluated for their propensity to form secondary-bonding interactions.…”
Section: Overviewmentioning
confidence: 99%